2022
DOI: 10.1136/bmjopen-2021-060209
|View full text |Cite
|
Sign up to set email alerts
|

Venerable vulnerability or remarkable resilience? A prospective study of the impact of the first wave of the COVID-19 pandemic and quarantine measures on loneliness in Swedish older adults with home care

Abstract: ObjectivesTo examine the early impact of the pandemic and of quarantine measures targeting older adults introduced in March 2020 on loneliness among older adults in Sweden.Design Prospective pretest–posttest and controlled interrupted time series designs.SettingThe population of older adults receiving home care before and during the emergence of the first COVID-19 pandemic wave in Sweden in Spring 2020.ParticipantsRespondents (n=45 123, mean age 85.6 years, 67.6% women) came from two waves of a total populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…On a population level, we observed similar levels of loneliness before and during the pandemic. This corroborates some findings [3,4] and contradicts others pointing to an increase in loneliness, particularly among those who were most at risk of social isolation and loneliness, including those receiving home care [18,19]. It is noteworthy that in the analysis of region as an explanatory factor in the likelihood of experiencing loneliness in 2021, Finland scored higher.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On a population level, we observed similar levels of loneliness before and during the pandemic. This corroborates some findings [3,4] and contradicts others pointing to an increase in loneliness, particularly among those who were most at risk of social isolation and loneliness, including those receiving home care [18,19]. It is noteworthy that in the analysis of region as an explanatory factor in the likelihood of experiencing loneliness in 2021, Finland scored higher.…”
Section: Discussionsupporting
confidence: 86%
“…One reason might be related to the timing of our data collection, which began in the early phase of the third wave of the pandemic, and that social-distancing strategies were less strict in the mid-autumn of 2021. The timing of data collection during the pandemic related to the findings is an issue discussed by, for example, Gustafsson et al [19]. Further, it could be related to adaptation and new ways of performing different leisure activities [22], including small-group and online leisure events and outdoor social gatherings [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses were performed separately for the 2019 (before the pandemic) and 2020 (during the pandemic) surveys, as well as collapsed for comparison of estimates between the years. Collapsing all observations within each year was chosen as previous studies on the same population have found no specific loneliness impact attributable to the introduction of restrictive policies among either home care recipients ( Gustafsson et al, 2022a ) or nursing home residents ( Gustafsson et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…While there has recently been increased attention paid to loneliness within the sociology of health and illness (Achdut & Refaeli, 2020; Malli et al., 2022; Petersen et al., 2020), the field has tended to concentrate on bereavement, ageing and the effects of social restrictions following COVID‐19 (Gustafsson et al., 2022; Patulny & Bower, 2022). Lockdown research is driven by an exceptional social, medical and political event, rather than the everyday experiences of people living with contested chronic and disabling conditions.…”
Section: Illness and Loneliness Experiencesmentioning
confidence: 99%